Intragenic regulation of SOCS3 isoforms - Oliver Klepsch; Lise Sarah Namer; Nadine Köhler; Raymond Kaempfer; Anna Dittrich; Fred Schaper (Cell Communication and Signaling, 2019)
Abstract Background Inflammatory reactions are commonly affected by stress responses. Interleukin-6 signalling is part of the inflammatory response and is stringently regulated by the feedback inhibitor SOCS3 expressed in a short and long isoform. Here, we studied the inhibitory potential of the two SOCS3 isoforms. Furthermore, we analysed the regulation of SOCS3 isoform expression and the role of PKR stress kinase signalling in SOCS3 protein expression. Methods We performed Western blotting, reporter assays, genetic analyses and manipulations for studying SOCS3 isoform expression and activation of signalling components involved in interleukin-6-induced and PKR-dependent signalling. Results Interleukin-6-induced endogenous expression of both SOCS3 isoforms was found in distinct cell types. Forced expression of either the long or short SOCS3 isoform demonstrated equal inhibitory activity of each isoform and confirmed longer half-life of the short isoform. Study of intragenic regulation of SOCS3 isoform expression revealed that (i) the 5′-UTR of SOCS3 mRNA restrains specifically expression of the long SOCS3 isoform, (ii) expression of the long isoform restrains expression of the short isoform, and (iii) signalling through the stress kinase PKR does not impact on SOCS3 isoform ratio. Conclusions Both SOCS3 isoforms show a similar potential for inhibiting interleukin-6 signalling but differ in their half-lives. Relative expression of the isoforms depends on intragenic elements yet is independent of PKR signalling. Graphic abstract